Effect of Climate on Fruit Color and Quality - Stanekzai, Noor Mohammad (Journal of Natural Sciences – Kabul University, 2023)
Fruit color and quality of two important factors of fruits. Its choose fruit harvesting time and help with the farmers, light color of fruit is the sign of more carbohydrate in fruit. Even though harvesting time effect on fruit quality, quantity, color, acidity, firmness, texture, juiciness, flavor, nutritional value and etc.; climate and climatic factors are also important for that, like sun light bring bloody, purple, red, yellow colors in fruit, therefore fruits which have red and bloody color has to receive shiny sun light for 3 weeks because in that time these fruits have need 23% glossy sun light.